Preventive and curative aspect of shimbi dhanya varga (pulses) w.s.r. to calcium deficiency - Kshirsagar, Shubhangi S.; Thatere (Wasnik), Vidya A.; Patrikar, V. G. (Ayurline: International Journal of Research in Indian Medicine, 2017)
Calcium is important for optimal bone health throughou thumans life.Also Phosphrous and Magnesium are among minerals and they have an important role in the bone metabolism. If we don’t get enough Calcium, you could face the problems related to weak bone, child ren may not reach their full potential adult height and adult may have low bone mass, which is a risk factor for osteoporosis. In recent years, use of medicinal Calcium is increased, because the community has become concerned about Calcium deficiency in their bone health. In Ayurved Samhitas, there is a brief description about various Aahar vargas (Naturally nourishing food). Shimbi varga (Pulses) is one of them. According to Ayurveda most of dravyas of Shimbi varga are vatashamak and Vata resides in Asthi dhatu. According to modern science Asthi (bone) is main site of Calcium. Shimbi varga contains rich amount of Ca, P, Mg and proteins & which is necessary for bone health. If we get these minerals from our diet, they are more effective and they are easily available and has no side effects. Therefore the use of these pulses in regular diet shows preventive and curative aspect in Calcium deficiency disorders.